Synthesis of Nano-Cadmium Sulfide Using Urea as a Capping Agent - et. al, Roshani Bhagat (International Journal of Advanced Science and Technology, 2019)
Abstract: Cadmium sulfide has been synthesized using chemical solution method having average particle size 20 nm. CdS nanoparticles are prepared by using urea as a capping agent and variety of techniques like X-Ray Diffraction (XRD), Tanning Electron Microscopy (TEM), and Fourier Transform Infrared Spectroscopy (FTIR) are used to carry out structural characterization of the nanoparticles.